«Et valeat tacitis scribere quisque notis». A emblemática presença de Alciato nos comentários aos Lusíadas de D. Marcos de S. Lourenço - Araújo, Filipa (2012)
In order to rescue from anonymity one of the commentaries to the camonian epic poem written in the seventeenth century, this study proposes a particular approach to the philological essence of the text composed by D. Marcos de S. Lourenço, underlining one of its specific differences from the contemporaneous critics – the systematic use of emblematics to decode the visual symbolism of the epopee. The analysis of different mechanisms used by the erudite friar to introduce the emblems in his reading can provide new information about the sources and demonstrate the documental value of this codex to the camonian studies, since its capacity to recognize the emblematic heritage in the Lusiadas’ iconographical morphology confirms the poet’s empathy with the European literary, artistic and cultural tendencies and exemplifies the fertile contaminatio among the modern pieces of literature in the camonian age.